Perancangan Website Outlet Mumu Ice Drink Untuk Pengembangan Pemasaran Dan Promosi Produk - Harma Hunaini; Nurainun; Triana Wulandari (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
The influence of current technology can change the marketing strategies of all business people. Where the right business strategy in this advanced era will advance the business. This encourages business people to adopt innovative marketing strategies, especially through online media. This article documents the design of business promotion through web creation for MSMEs. In this project, we chose the Web platform as the main development tool for creating website designs. Several stages of website creation are data collection, system analysis, website design using a toolplate platform. This project aims to increase product exposure, expand market reach, and improve the marketing and product promotion process for UMKM. The result of implementing this project is in the form of a website. This project is expected to be useful for UMKM by increasing the number of customers.